CD27+ B cells from a subgroup of common variable immunodeficiency patients are less sensitive to apoptosis rescue regardless of interleukin‐21 signalling. (8th September 2013) - Clemente, A.; Pons, J.; Lanio, N.; Matamoros, N.; Ferrer, J. M.
Summary Common variable immunodeficiency (CVID) is a primary immunodeficiency characterized by hypogammaglobulinaemia and recurrent infections. Although the underlying cause is unknown, B cells from most CVID patients fail to differentiate to memory or plasma cells. We investigated if increased apoptosis could influence the fate of B cells. For this purpose we activated purified B lymphocytes of CVID patients with a surrogate T‐dependent (anti‐CD40) or T‐independent [cytosine–phosphate–guanosine oligodeoxynucleotides (CpG‐ODN) or anti‐immunoglobulin (Ig)M)] stimulus with or without interleukin (IL)‐21. We found that CD27+ B cells were more sensitive than CD27– B cells to spontaneous apoptosis and less sensitive to rescue from apoptosis. The addition of IL‐21 down‐modulated the protective effect of all the stimuli on CD27– B cells and the protective effect of CpG‐ODN and anti‐IgM on CD27+ B cells. In contrast, IL‐21 rescued unstimulated CD27– B cells and improved the rescue of anti‐CD40‐stimulated CD27+ B cells. When we compared patients and controls, mainly CD27+ B cells from MB0 patients were less sensitive to rescue from apoptosis than those from MB1 patients and controls after activation, irrespective of the IL‐21 effect. Increased apoptosis during an immune response could result in lower levels of immunoglobulin production in these patients.